Chorioretinal temperature monitoring during transpupillary thermotherapy for choroidal neovascularisation - Miura, S (Copyright 2005 British Journal of Ophthalmology, 2005)
Aims: To investigate the difference in temperature rise between normal choroid and choroidal revascularisation (CNV) during transpupillary thermotherapy (TTT) and the relation between laser spot size and power in the rat fundus. Methods: A modified slit lamp, which was installed with two laser wavelengths (490 nm for illumination and fluorescein excitation and 810 nm for hyperthermia), was developed for TTT and temperature monitoring. Temperature rise during TTT was monitored by observing fluorescence released from thermosensitive liposomes encapsulating carboxyfluorescein. Two types of liposomes were prepared; their phase transition temperatures were 40°C and 46°C, respectively. Laser power settings required to observe fluorescence released from 46°C liposome in normal choroid or CNV were compared. Next, the power settings with 0.5 mm and 0.25 mm spot sizes were compared following administration of 40°C liposome or 46°C liposome. Results: The minimum power values when release from 46°C liposome was observed showed a significant difference in distribution of power values between normal choroid and CNV. CNV required significantly higher power than normal choroid. With 40°C liposome, the power was 9.7 (1.9) mW (mean (SD)) at a spot size of 0.25 mm, and 12.1 (1.6) mW at 0.5 mm, respectively. When using 46°C liposome, the power setting was 10.2 (1.2) mW at a spot size of 0.25 mm, and 14.6 (2.2) mW at 0.5 mm, respectively. Conclusions: CNV demonstrated varying heat conduction, compared with normal choroid. Laser power required to raise the temperature should not necessarily be doubled, even when the spot size is doubled. Close attention should be given to the selection of power settings when performing TTT for CNV.